Optimising the Demographic Bonus for Cultural Resilience in Indonesia’s National Identity in the Global Era - Maulidya, Ikcha; Sutanto (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study examines the strategic utilisation of Indonesia’s demographic bonus to enhance cultural resilience. It explores how the youth population, as the largest productive demographic group, can be mobilised to preserve, adapt, and innovate traditional cultural practices amidst globalisation and societal transformations. The study also analyses how policy interventions, education, and digital advancements can ensure cultural sustainability and strengthen national identity for future generations. Study Design/Methodology/Approach: This research adopts a qualitative approach, employing a literature review and case study analysis. Data were collected through an extensive review of demographic trends, national policies, and cultural resilience strategies. Case studies from Indonesia and other nations that have successfully leveraged their demographic bonuses were examined to draw comparative insights Findings: The findings reveal that Indonesia’s demographic bonus presents both opportunities and challenges in maintaining cultural resilience. Strategies such as integrating cultural values into education, empowering youth through creative industries, and leveraging digital platforms for cultural promotion are essential. The study highlights the importance of multi-sector collaboration, involving government policies, community engagement, and private sector support to create a sustainable cultural ecosystem.Top of FormBottom of Form Originality/Value: This study contributes to the growing discourse on cultural resilience by establishing a direct link between demographic dividend management and cultural sustainability. It offers innovative policy recommendations for integrating cultural education, digital engagement, and youth empowerment to ensure Indonesia’s cultural heritage remains robust amid globalisation and social change. The study provides practical insights for policymakers, educators, and cultural stakeholders to optimise the demographic bonus as a strategic asset for national cultural development.